Analisis perbandingan tingkat inflasi di Kota Manado dan daerah perdesaan di Sulawesi Utara - Norma O. F. Regar; Caroline B.D. Pakasi; Grace A. J. Rumagit (AGRI-SOSIOEKONOMI, 2016)
This study aims to: (1) Describe the inflation rate in the city of Manado and rural areas in the province of North Sulawesi; (2) to analyze the comparative rate of inflation that occurred in the city of Manado and rural areas in the province of North Sulawesi; (3) To analyze the effect of the inflation rate of each group of public spending to the inflation rate in the city of Manado and rural areas in the province of North Sulawesi. The research was conducted in the city of Manado North Sulawesi for 3 (three) months. The data used is inflation data from January 2009 to December 2014, which analyzed qualitative, and quantitative descriptive in the statistical analysis using different test average analysis and multiple linear regression. The results showed that the average inflation rate for rural areas is relatively high compared with urban areas. seven groups of grouping expenditure in the inflation calculation period 2009-2014 showed that there are four groups that the inflation average rate is higher in cities than in rural, which includes foodstuffs, housing, electricity, gas and fuel; education, recreation and sports; and group transport, communications and financial services. The rest, three other groups show the average inflation rate in the city is lower than in rural areas, which include: food, beverages, cigarettes and tobacco; clothing; and health groups. The inflation rate in the city of Manado produces the same patterns with the rate of inflation in the rural areas. The rate of general inflation both in the city of Manado and rural areas is strongly influenced by the inflation rate of seven groups of expenditure for goods and services which consist of foodstuffs, food, clothing, housing, health, education and transport.